A cellulose paper-based separator for zinc-iodine battery and a preparation method and application thereof

CN121440030BActive Publication Date: 2026-10-30SOUTH CHINA UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511667797.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-11-14
Publication Date
2026-10-30
Estimated Expiration
2045-11-14

AI Technical Summary

Technical Problem

[0005]为解决现有锌碘电池聚碘化物的穿梭效应以及锌枝晶问题,本发明的首要目的在于提供一种用于锌碘电池的纤维素纸基隔膜材料

Benefits of technology

本发明通过三层复合结构设计的纤维素纸基隔膜,实现了抑制聚碘化物穿梭和稳定锌负极的高性能长寿命锌碘电池。对于正极,两侧致密的氧化纳米纤维素(TOCN)层通过纳米级孔径物理筛分、表面负电官能团的静电排斥以及极性基团的化学吸附三重协同机制,极大程度地抑制了聚碘化物的穿梭效应,有效减少了活性物质的损失和自放电。同时,TOCN层其均匀的纳米孔道能引导Zn²⁺离子流均匀分布,实现锌的无枝晶均匀沉积;中间的纸浆基体层则提供了优异的机械强度,能有效抵抗枝晶的刺穿,从而同步提升了锌负极的循环稳定性和安全性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121440030B_ABST
    Figure CN121440030B_ABST
Patent Text Reader

Abstract

The application discloses a cellulose paper-based diaphragm for a zinc-iodine battery and a preparation method and application thereof. The diaphragm is a three-layer composite structure, comprising a base layer composed of paper pulp fibers such as conifer pulp, broadleaf pulp, bamboo pulp or straw pulp through a wet papermaking technology, and dense functional layers composed of oxidized nanocellulose (TOCN) on both sides of the base layer. The preparation method mainly comprises the following steps: firstly, preparing a paper-based diaphragm base through wet papermaking; secondly, coating a TOCN water dispersion on both sides of the diaphragm base; and finally, performing heat pressing and drying treatment to tightly combine the three layers. The diaphragm can simultaneously realize physical blocking and electrostatic repulsion of polyiodide ions by utilizing the nanopore diameter and surface negative functional groups of the TOCN layer, so that the shuttling effect is effectively inhibited; and the uniform pore channel can also guide uniform deposition of zinc ions and inhibit dendrite growth. The diaphragm is green in raw material, simple in process and low in cost, and can significantly improve the cycle life and coulombic efficiency of the zinc-iodine battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of secondary battery technology, specifically relating to the preparation technology of functional separators for zinc-iodine batteries, and particularly to a cellulose paper-based separator for zinc-iodine batteries, its preparation method and application. Background Technology

[0002] Aqueous zinc-iodine batteries have broad application prospects in large-scale energy storage due to their high theoretical capacity, high safety, and environmental friendliness. However, the development of this system is limited by two key technical challenges. One is the formation of polyiodide (I3) on the positive electrode side. - The dissolution and shuttle effect of zinc anodes in electrolytes (such as those for hydrogen evolution, hydrogen evolution, and corrosion) leads to irreversible loss of active materials, severe self-discharge, and low coulombic efficiency. Zinc anodes are prone to dendrite growth, hydrogen evolution, and corrosion in aqueous electrolytes, causing short circuits and capacity decay in the battery.

[0003] Currently, glass fiber (GF) membranes, widely used in zinc-iodine batteries, possess good electrolyte wettability and high porosity, but their uneven pore size distribution and excessively large pore sizes (micrometer scale) prevent effective blocking of polyiodide ion migration. Furthermore, the chemical inertness of the GF membrane surface offers no regulatory effect on zinc deposition behavior. Some studies have attempted to improve performance using surface modification or composite membranes, but these approaches suffer from complex processes, high costs, or limited functionality, making it difficult to simultaneously address the issues on both the positive and negative electrodes.

[0004] Cellulose is the most abundant natural polymer material in the world, possessing advantages such as renewability, biodegradability, and low cost. Oxidized nanocellulose (TOCN), with its nanoscale fiber diameter, high specific surface area, abundant surface functional groups (such as carboxyl groups), and excellent mechanical properties, provides an ideal platform for constructing multifunctional separators. Therefore, developing a high-performance separator suitable for zinc-iodine batteries using cellulose as a raw material through a green and simple process has significant research value and practical significance. Summary of the Invention

[0005] To address the shuttle effect of polyiodides and the zinc dendrite problem in existing zinc-iodine batteries, the primary objective of this invention is to provide a cellulose paper-based separator material for zinc-iodine batteries. This material can effectively suppress polyiodide shuttle and stabilize the zinc anode.

[0006] Another object of the present invention is to provide a method for preparing a cellulose paper-based separator material for zinc-iodine batteries.

[0007] Another object of the present invention is to provide the application of the above-mentioned cellulose paper-based separator in zinc-iodine batteries.

[0008] The objective of this invention is achieved through the following technical solution: A method for preparing a cellulose paper-based separator material for zinc-iodine batteries, comprising the following steps: (1) Preparation of pulp fiber pulp and oxidized nanocellulose aqueous dispersion; (2) Using the pulp fiber slurry as raw material, a paper-based diaphragm matrix layer is prepared by wet papermaking technology; (3) The oxidized nanocellulose aqueous dispersion is uniformly coated on both sides of the paper-based membrane substrate layer obtained in step (2); (4) The coated diaphragm is subjected to hot pressing and drying treatment to obtain the cellulose paper-based diaphragm.

[0009] Furthermore, in step (1), the pulp fiber and oxidized nanocellulose raw materials include, but are not limited to, one or more of softwood pulp, hardwood pulp, bamboo pulp, and straw pulp.

[0010] Furthermore, in step (1), the pulp fibers in the pulp fiber slurry are subjected to beating treatment, and the beating degree is 30-70°SR, more preferably 45-70°SR.

[0011] Further, in step (1), the oxidized nanocellulose aqueous dispersion is prepared by the following steps: oxidized nanocellulose with a surface rich in carboxyl groups is obtained by TEMPO oxidation, and then the oxidized nanocellulose is dispersed in water to obtain the oxidized nanocellulose aqueous dispersion; the solid content of the oxidized nanocellulose aqueous dispersion is 0.1%-1.3%.

[0012] The oxidized nanocellulose has an aspect ratio of 210-450 and an oxidation degree of 0.6-1.3 mmol / g. Analysis of the experimental data revealed that, in this invention, when the solid content of the oxidized nanocellulose dispersion is the same, the aspect ratio, length, oxidation degree, and other parameters of the oxidized nanocellulose have no significant impact on the performance of the membrane.

[0013] Furthermore, in step (2), the wet papermaking technology includes, but is not limited to, the Kaiser process, the long-wire papermaking process, the cylinder papermaking process, or the inclined wire papermaking process.

[0014] Furthermore, in step (2), the basis weight of the paper-based diaphragm matrix layer is 30-80 g / m³. 2 More preferably 55-80g / m 2 .

[0015] Furthermore, in step (3), by controlling the number of coating cycles or the amount of coating, the areal density of the functional layer on one side is made to be 0.01-0.5 mg / cm³. 2 More preferably 0.2-0.5 mg / cm³ 2 .

[0016] Furthermore, in step (4), the temperature of the hot-press drying treatment is 60-120 ℃, the pressure is 1-10 MPa, and the time is 5-60 minutes; more preferably, the temperature is 90-120 ℃, the pressure is 2-8 MPa, and the time is 10-60 minutes.

[0017] Furthermore, the total thickness of the cellulose paper-based separator is 20-90 μm, more preferably 55 μm.

[0018] Furthermore, the present invention also discloses a cellulose paper-based separator for zinc-iodine batteries, which is prepared by the aforementioned method.

[0019] Furthermore, the present invention also discloses a zinc-iodine battery assembled from the above-mentioned cellulose paper-based separator.

[0020] Compared with the prior art, the present invention has the following advantages and beneficial effects: This invention achieves a high-performance, long-life zinc-iodine battery by using a three-layer composite structure cellulose paper-based separator to suppress polyiodide shuttle and stabilize the zinc anode. For the positive electrode, the dense oxidized nanocellulose (TOCN) layers on both sides, through a triple synergistic mechanism of physical sieving of nanoscale pores, electrostatic repulsion of negatively charged functional groups on the surface, and chemical adsorption of polar groups, greatly suppress the shuttle effect of polyiodides, effectively reducing the loss of active material and self-discharge. At the same time, the uniform nanopores of the TOCN layer can guide the uniform distribution of Zn²⁺ ion flow, achieving dendrite-free uniform deposition of zinc; the middle pulp matrix layer provides excellent mechanical strength, effectively resisting dendrite penetration, thereby simultaneously improving the cycle stability and safety of the zinc anode.

[0021] All core raw materials used in this invention are cellulose (such as wood pulp, bamboo pulp, and straw pulp), which are widely available, renewable, biodegradable, and extremely low in cost. The entire preparation process uses water as a solvent, eliminating the need for toxic or harmful organic solvents, making it safe, environmentally friendly, and in line with the development concept of green chemistry.

[0022] The wet papermaking technology (such as the Kaiser process, cylinder papermaking, etc.), coating process, and hot pressing process used in this invention are all very mature and easily scaled-up technologies in the papermaking and materials industry. This makes the path from laboratory to industrial production very smooth, with low equipment investment, controllable production costs, and huge commercial application potential and market competitiveness. Attached Figure Description

[0023] To more clearly illustrate the technical solutions adopted in the embodiments of the present invention or the prior art, the accompanying drawings involved in the description of the embodiments or the prior art will be briefly introduced below. It should be noted that these drawings only represent some embodiments of the present invention, and those skilled in the art can derive other related drawings based on these drawings without creative effort.

[0024] Figure 1 These are scanning electron microscope images of the paper-based diaphragms prepared in Example 1 and Comparative Example 1 of the present invention; Figure 2 Mechanical tensile stress-strain curves of the paper-based diaphragms prepared in Example 1 and Comparative Example 10 of this invention; Figure 3 The figures show the charge-discharge curves of zinc-iodine batteries assembled with paper-based separators prepared in Examples 1, 1, and 4 of this invention. The experimental results are all stable data obtained by repeating the experiment three times. Figure 4 The figures show the rate performance of zinc-iodine batteries assembled with paper-based separators prepared in Example 1, Comparative Example 1, and Comparative Example 4 of this invention. The experimental results are all stable data obtained by repeating the experiment three times. Figure 5 The figure shows the cycling stability of zinc-iodine batteries assembled with paper-based separators prepared in Example 1, Comparative Example 1 and Comparative Example 4 of the present invention at a current density of 1 A / g. The experimental results are all stable data repeated three times. Figure 6 The zinc-iodine batteries assembled with paper-based separators prepared in Examples 1, 1, and 4 of this invention achieved a speed of 1 mA / cm². 2 The time-voltage long-cycle plots under current density show that the experimental results are all stable data obtained by repeating the experiment three times. Figure 7 The zinc ion transport number diagram is for the zinc symmetric battery assembled with the paper-based separator prepared in Example 1 of the present invention. All experimental results are stable data obtained by repeating the experiment three times. Figure 8 The zinc ion transport number diagram is shown for the zinc ion symmetric battery assembled with the paper-based separator prepared in Comparative Example 1 of this invention. All experimental results are stable data obtained by repeating the experiment three times. Figure 9 The figure shows the zinc ion transport number of the zinc symmetric battery assembled with the paper-based separator prepared in Comparative Example 4 of this invention. All experimental results are stable data obtained by repeating the experiment three times.

[0025] The realization of the objective, functional features and advantages of the present invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation

[0026] To clearly demonstrate the objectives, technical solutions, and advantages of the embodiments of the present invention, the technical solutions in the embodiments of the present invention will be comprehensively and accurately described below. It should be understood that the following embodiments are only for illustrating the present invention and are not intended to limit it. Unless otherwise expressly stated, all technical and scientific terms used herein follow the general definitions within the technical field, and all reagents mentioned meet industrial or analytical purity standards. Furthermore, the accompanying drawings and descriptions are intended to help those skilled in the art to deeply understand this application, and are not intended to limit the subject matter covered by the claims.

[0027] Regarding the "range" mentioned in this application, it is defined by setting a lower limit and an upper limit, which define the boundaries of a specific range. Such a range may or may not include its endpoints, and can be freely combined; that is, any lower limit can be combined with any upper limit to form a new range.

[0028] Unless otherwise specified, all embodiments and their optional solutions in this application can be combined with each other to create new technical solutions. Similarly, unless otherwise specified, all technical features and their optional features in this application can also be combined with each other to form new technical solutions.

[0029] The present invention will now be described in detail, and includes the following specific steps: (1) Preparation of pulp fiber pulp and oxidized nanocellulose aqueous dispersion; (2) Using the pulp fiber slurry as raw material, a paper-based diaphragm matrix layer is prepared by wet papermaking technology; (3) The oxidized nanocellulose aqueous dispersion is uniformly coated on both sides of the paper-based membrane substrate layer obtained in step (2); (4) The coated diaphragm is subjected to hot pressing and drying treatment to obtain the cellulose paper-based diaphragm.

[0030] The performance analysis and testing of the three-layer composite cellulose paper-based separator materials prepared in the various embodiments and comparative examples of the present invention are as follows: Electrochemical performance testing: A CR2025 coin cell zinc-iodine battery was assembled using a cellulose paper-based separator with a three-layer composite structure. The positive electrode was iodine-loaded activated carbon, the negative electrode was zinc foil, and the electrolyte was 2M ZnSO4. The battery's long-cycle performance and rate performance at a current density of 1 A / g were tested.

[0031] The galvanostatic charge-discharge (GCD) test was conducted on the Blue Electric button battery testing system. The test procedure was to discharge first and then charge, with the charge and discharge test currents sequentially set to 0.5 A / g, 1.0 A / g, 3 A / g, 5 A / g, 10 A / g, and 0.5 A / g. The battery was cycled 8 times at each current density to obtain the rate performance curve of the prepared material. The corresponding cycle stability test was performed by setting the current density to 1 A / g and cycling 2000 times.

[0032] Ion transport number testing. The ion transport number of the cell was calculated by electrochemical impedance spectroscopy (EIS) and current-time curve (it curve). The cell used in the test was a zinc symmetric cell. The frequency range of the electrochemical impedance spectroscopy test was set to 0.01-100000 Hz, and the amplitude was 10 mV. The applied voltage for the current-time curve test was 10 mV, the test time was 1500 s, and the sampling interval was 1 s.

[0033] Example 1 (1) Pulp made by beating softwood pulp to 45 °SR. A TOCN aqueous dispersion with a solid content of 0.5 wt% was prepared from the same softwood pulp using the TEMPO oxidation method; (2) Using the Kaiser process automatic papermaking system, pulp with an oven-dry weight of 1.57 g is formed into a wet paper-based diaphragm matrix with a basis weight of 55 g / m². 2 ; (3) Using a scraping method, a certain amount of TOCN dispersion is coated on both the upper and lower sides of the wet paper-based diaphragm substrate (the density on one side is controlled to be ~0.2 mg / cm). 2 ); (4) The coated wet film was placed in a hot press and hot-pressed at 90 °C and 5 MPa for 10 minutes to obtain a cellulose paper-based separator with a thickness of approximately 55 μm. As shown in Table 1, the capacity retention rate of the zinc-iodine battery assembled with the separator prepared in this embodiment after 2000 cycles at a current density of 1 A / g was 94%, and the capacity retention rate of the assembled zinc-zinc symmetric battery after 1 mA / cm² was 94%. 2 The time-voltage cycle time at current density is 1800 h.

[0034] Example 2 The preparation process is the same as in Example 1, except that the pulp raw material is changed from softwood pulp to hardwood pulp. As shown in Table 1, the membrane-assembled zinc-iodine battery prepared in this example retains 87% of its capacity after 2000 cycles at a current density of 1 A / g, and the assembled zinc-zinc symmetric battery retains 87% of its capacity after 1 mA / cm² cycles. 2 The time-voltage cycle time at the current density is 1215h.

[0035] Example 3 The preparation process is the same as in Example 1, except that the pulp raw material is changed from softwood pulp to bamboo pulp. As shown in Table 1, the membrane-assembled zinc-iodine battery prepared in this example retains 77% of its capacity after 2000 cycles at a current density of 1 A / g, and the assembled zinc-zinc symmetric battery retains 77% of its capacity after 1 mA / cm² cycles. 2 The time-voltage cycle time at the current density is 701 h.

[0036] Example 4 The preparation process is the same as in Example 1, except that the pulp raw material is changed from softwood pulp to a mixed pulp of softwood and hardwood pulp. As shown in Table 1, the membrane-assembled zinc-iodine battery prepared in this example retains 89% of its capacity after 2000 cycles at a current density of 1 A / g, and the assembled zinc-zinc symmetric battery retains 89% of its capacity after 1 mA / cm² cycles. 2 The time-voltage cycle time at the current density is 885 h.

[0037] Example 5 The preparation process is the same as in Example 1, except that the pulp beating degree is changed to 30°SR. As shown in Table 1, the capacity retention rate of the membrane-assembled zinc-iodine battery prepared in this example after 2000 cycles at a current density of 1 A / g is 51%, and the capacity retention rate of the assembled zinc-zinc symmetric battery at 1 mA / cm² is... 2 The time-voltage cycle time at the current density is 192 h.

[0038] Example 6 The preparation process is the same as in Example 1, except that the pulp freeness is changed to 70°SR. As shown in Table 1, the capacity retention rate of the membrane-assembled zinc-iodine battery prepared in this example after 2000 cycles at a current density of 1 A / g is 81%, and the capacity retention rate of the assembled zinc-zinc symmetric battery at 1 mA / cm² is... 2 The time-voltage cycle time at current density is 730 h.

[0039] Example 7 The preparation process is the same as in Example 1, except that the basis weight of the membrane substrate is changed to 80 g / m³. 2 As shown in Table 1, the membrane-assembled zinc-iodine battery prepared in this embodiment retained 77% of its capacity after 2000 cycles at a current density of 1 A / g, and the assembled zinc-zinc symmetric battery retained 77% of its capacity at a current density of 1 mA / cm². 2 The time-voltage cycle time at the current density is 602 h.

[0040] Example 8 The preparation process is the same as in Example 1, except that the coating amount of TOCN on one side is changed to achieve a density of 0.05 mg / cm³ on one side. 2 As shown in Table 1, the membrane-assembled zinc-iodine battery prepared in this embodiment retained 68% of its capacity after 2000 cycles at a current density of 1 A / g, and the assembled zinc-zinc symmetric battery retained 68% of its capacity after 1 mA / cm² cycles. 2 The time-voltage cycle time at the current density is 568 h.

[0041] Example 9 The preparation process is the same as in Example 1, except that the coating amount of TOCN on one side is changed to achieve a density of 0.4 mg / cm³ on one side. 2 As shown in Table 1, the membrane-assembled zinc-iodine battery prepared in this embodiment retained 70% of its capacity after 2000 cycles at a current density of 1 A / g, and the assembled zinc-zinc symmetric battery retained 70% of its capacity at a current density of 1 mA / cm². 2 The time-voltage cycle time at the current density is 10¹⁷ h.

[0042] Example 10 The preparation process was the same as in Example 1, except that the hot-pressing parameters were changed to 100 °C, 2 MPa, and 30 minutes. As shown in Table 1, the membrane-assembled zinc-iodine battery prepared in this example retained 84% of its capacity after 2000 cycles at a current density of 1 A / g, and the assembled zinc-zinc symmetric battery retained 84% of its capacity after 1 mA / cm² cycles. 2 The time-voltage cycle time at current density is 1200h.

[0043] Example 11 The preparation process is the same as in Example 1, except that the hot-pressing process parameters are changed to 60°C, 8 MPa, and 60 minutes. As shown in Table 1, the membrane-assembled zinc-iodine battery prepared in this example has a capacity retention rate of 83% after 2000 cycles at a current density of 1 A / g, and the assembled zinc-zinc symmetric battery has a capacity retention rate of 1 mA / cm². 2 The time-voltage cycle time at the current density is 988 h.

[0044] Comparative Example 1 The preparation process is the same as in Example 1, except that after papermaking using the Kaiser process, the same hot-pressing treatment is performed directly without coating with a TOCN layer to obtain a pure pulp separator. As shown in Table 1, the separator prepared in this comparative example exhibits a 63% capacity retention rate after 2000 cycles at a current density of 1 A / g for assembled zinc-iodine batteries, and a capacity retention rate of 1 mA / cm² for assembled zinc-zinc symmetric batteries. 2 The time-voltage cycle time at the current density is 434 h.

[0045] Comparative Example 2 The preparation process is the same as in Example 1, except that the pulping process is omitted, and unpulped softwood pulp is used directly to prepare the pulp and form the pulp matrix. As shown in Table 1, the capacity retention rate of the membrane-assembled zinc-iodine battery prepared in this comparative example after 2000 cycles at a current density of 1 A / g is 61%, and the capacity retention rate of the assembled zinc-zinc symmetric battery at 1 mA / cm² is... 2 The time-voltage cycle time at the current density is 501 h.

[0046] Comparative Example 3 The preparation process is the same as in Example 1, except that the TOCN dispersion is filtered into a membrane in a single step and then directly subjected to the same hot-pressing treatment to obtain a pure TOCN membrane. The zinc-iodine battery assembled with the separator prepared in this comparative example exhibits rapid failure at a current density of 1 A / g, while the assembled zinc-zinc symmetric battery fails at 1 mA / cm². 2 Rapid failure at current density.

[0047] Comparative Example 4 The preparation process is the same as in Example 1, except that in step (3), the TOCN dispersion is replaced with an equal amount and concentration of ordinary nanocellulose (unoxidized) dispersion. As shown in Table 1, the capacity retention rate of the membrane-assembled zinc-iodine battery prepared in this comparative example after 2000 cycles at a current density of 1 A / g is 74%, and the capacity retention rate of the assembled zinc-zinc symmetric battery at 1 mA / cm 2 The time-voltage cycle time at current density is 996 h.

[0048] Comparative Example 5 The preparation process is the same as in Example 1, except that equal amounts of pulp fiber slurry and TOCN dispersion are uniformly mixed and then directly used to prepare paper-based separators. As shown in Table 1, the capacity retention rate of the zinc-iodine battery assembled with the separator prepared in this comparative example after 2000 cycles at a current density of 1 A / g is 62%, and the capacity retention rate of the assembled zinc-zinc symmetric battery at 1 mA / cm² is... 2 The time-voltage cycle time at the current density is 352 h.

[0049] Comparative Example 6 The preparation process is the same as in Example 1, except that in step (3), a polyvinyl alcohol aqueous solution of the same concentration as the TOCN dispersion is used instead of the TOCN dispersion for double-sided coating. As shown in Table 1, the capacity retention rate of the membrane-assembled zinc-iodine battery prepared in this comparative example after 2000 cycles at a current density of 1 A / g is 70%, and the capacity retention rate of the assembled zinc-zinc symmetric battery after 1 mA / cm 2 The time-voltage cycle time at the current density is 871 h.

[0050] Comparative Example 7 The preparation process is the same as in Example 1, except that in step (3), TOCN dispersion is coated only on one side of the pulp matrix. As shown in Table 1, the capacity retention of the membrane-assembled zinc-iodine battery prepared in this comparative example after 2000 cycles at a current density of 1 A / g is 48%, and the capacity retention of the assembled zinc-zinc symmetric battery at 1 mA / cm 2 The time-voltage cycle time at the current density is 325 h.

[0051] Comparative Example 8 The preparation process is the same as in Example 1, except that in step (4), room temperature air drying is used instead of hot pressing drying. As shown in Table 1, the capacity retention rate of the membrane-assembled zinc-iodine battery prepared in this comparative example after 2000 cycles at a current density of 1 A / g is 85%, and the capacity retention rate of the assembled zinc-zinc symmetric battery after 1 mA / cm² is 85%. 2 The time-voltage cycle time at current density is 720 h.

[0052] Comparative Example 9 The preparation process is the same as in Example 1, except that the basis weight of the membrane substrate is changed to 20 g / m³. 2 As shown in Table 1, the capacity retention of the membrane-assembled zinc-iodine battery prepared in this comparative example after 2000 cycles at a current density of 1 A / g was 73%, and the capacity retention of the assembled zinc-zinc symmetric battery at 1 mA / cm² was [missing information]. 2 The time-voltage cycle time at the current density is 97 h.

[0053] Comparative Example 10 This comparative example provides a commercial glass fiber separator. As shown in Table 1, the capacity retention of this separator in a zinc-iodine battery after 2000 cycles at a current density of 1 A / g is 82%, and the capacity retention of a zinc-zinc symmetric battery after 1 mA / cm² is [not specified]. 2 The time-voltage cycle time at the current density is 739 h.

[0054] Figure 1 The scanning electron microscope (SEM) image of the paper-based separator shows that the surface of the separator prepared in Example 1 is a dense and smooth layer of oxidized nanocellulose. The TOCN layer successfully filled the large pores between the pulp fibers of the separator prepared in Comparative Example 1, forming nanoscale fine pores.

[0055] Figure 2 Mechanical tensile stress-strain curves of the diaphragms prepared in Example 1 and Comparative Example 10. From... Figure 2 It can be seen that the tensile stress of the diaphragm prepared in Example 1 is 52.6 MPa, which is much greater than the tensile stress of the diaphragm prepared in Comparative Example 10 (1.8 MPa), indicating that the diaphragm prepared in Example 1 has excellent mechanical properties.

[0056] Figure 3 Charge-discharge curves of batteries assembled with three different separators at the same rate are shown. The curve of the separator prepared in Example 1 shows that it has the highest discharge specific capacity and the lowest polarization voltage. The curve of the separator prepared in Comparative Example 1 (pure pulp) shows a larger polarization voltage and a lower discharge specific capacity, indicating severe shuttle effect and side reactions. The performance of the separator prepared in Comparative Example 4 (unoxidized CNF) is between the two, demonstrating that the electrostatic repulsion and chemical anchoring of the carboxyl functional groups on the TOCN surface are crucial for reducing polarization and suppressing shuttle.

[0057] Figure 4 The rate performance of batteries assembled with three different separators was compared at various current densities. The battery assembled with the separator prepared in Example 1 exhibited the highest capacity at all current densities. Its capacity decay was minimal when the current density increased from a low rate to a high rate. When the current density returned to the initial low rate, the capacity was almost fully recovered, demonstrating excellent rate performance. The batteries assembled with separators prepared in Comparative Examples 1 and 4 had significantly lower capacities, more severe capacity decay, and poorer capacity recovery.

[0058] Figure 5 The long-term cycling performance of the battery at a current density of 1 A / g was recorded. The battery assembled with the separator prepared in Example 1 exhibited extremely stable cycling performance, with a capacity retention of 93% after 2000 cycles, indicating that the loss of active material and side reactions were effectively suppressed. In contrast, the battery assembled with the separator prepared in Comparative Example 1 showed rapid capacity decay, which is direct evidence of the continuous occurrence of polyiodide shuttle and side reactions. Although the battery assembled with the separator prepared in Comparative Example 4 was superior to Comparative Example 1, its capacity decay rate and coulombic efficiency stability were both inferior to those of Example 1, indicating the key role of functional groups introduced by oxidation treatment.

[0059] Figure 6 This demonstrates the long-cycle stability of the zinc-symmetric battery, used to evaluate the reversibility and dendrite suppression of the zinc anode. The membrane prepared in Example 1 maintained a flat, symmetrical voltage plateau throughout 1800 hours, with stable and extremely low overpotentials, indicating a highly reversible and uniform zinc deposition / dissolution process without dendrite growth or severe side reactions. In contrast, the membrane prepared in Comparative Example 1 quickly exhibited voltage fluctuations, short-circuit spikes, or continuously increasing overpotentials, indicating zinc dendrite formation and battery failure. The membrane prepared in Comparative Example 4 may perform better than Comparative Example 1 but worse than Example 1, demonstrating that the TOCN layer provides better stabilization for the zinc anode than ordinary CNF.

[0060] Figure 7 , 8 Figures 9 and 1 are zinc ion migration numbers of zinc symmetric batteries assembled with paper-based separators prepared in Examples 1, 1, and 4 of this invention, respectively. Figure 7Example 1 shows that it has the highest zinc ion transference number (0.644), indicating that its ion migration process is mainly driven by Zn. 2+ leading. Figure 8 (Comparative Example 1) and Figure 9 (Comparative Example 4) showed a significantly lower zinc ion migration number. This data demonstrates that the membrane of the present invention, through its dense and negatively charged TOCN layer, effectively restricts the migration of anions, thereby increasing the zinc ion migration number.

[0061] To better illustrate the differences between the various embodiments and comparative examples, the capacity retention of the membrane-assembled zinc-iodine batteries prepared in the embodiments and comparative examples after 2000 cycles at a current density of 1 A / g, and the capacity retention of the zinc-zinc symmetric batteries at 1 mA / cm² are compared. 2 The results of time-voltage cycle time (i.e., cycle life) under current density are summarized in Table 1.

[0062] Table 1 Test results of Examples 1-11 and Comparative Examples 1-10

[0063] As can be seen from the performance data of the examples and comparative examples, the performance optimization of the diaphragm of the present invention depends on the synergistic control of multiple process parameters. The differences in physical and chemical properties of different fiber raw materials (Examples 2-4) directly affect the microstructure of the diaphragm; the degree of beating determines the degree of microfibrillation of the fibers, affecting the bonding strength between fibers and the density of the diaphragm; while the matrix basis weight and the amount of nanocellulose coating jointly regulate the integrity of the functional layer and its ion transport behavior (Comparative Examples 1-9). The interaction of these factors collectively determines the final electrochemical performance of the diaphragm.

[0064] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.

Claims

1. A method for preparing a cellulose paper-based separator material for zinc-iodine batteries, characterized in that, Includes the following steps: (1) Preparation of pulp fiber slurry and oxidized nanocellulose aqueous dispersion; the pulp fibers in the pulp fiber slurry are subjected to beating treatment, and the beating degree is 45-70°SR; the solid content of the oxidized nanocellulose aqueous dispersion is 0.1%-1.3%; (2) A paper-based separator matrix layer is prepared using the pulp fiber slurry as raw material and wet papermaking technology; the basis weight of the paper-based separator matrix layer is 55-80 g / m³. 2 ; (3) The oxidized nanocellulose aqueous dispersion is uniformly coated on both sides of the paper-based membrane substrate layer obtained in step (2); the areal density of the functional layer on one side is 0.2-0.5 mg / cm³. 2 ; (4) The coated diaphragm is subjected to hot-press drying treatment at a temperature of 50-120 ℃, a pressure of 1-10 MPa, and a time of 5-60 minutes to obtain the cellulose paper-based diaphragm; the thickness of the cellulose paper-based diaphragm is 20-90 μm.

2. The method according to claim 1, characterized in that, In step (1), the pulp fiber and oxidized nanocellulose raw materials include one or more of softwood pulp, hardwood pulp, bamboo pulp and straw pulp.

3. The method according to claim 1, characterized in that, In step (1), the oxidized nanocellulose with a surface rich in carboxyl groups, which is obtained by TEMPO oxidation, is dispersed in water to obtain an aqueous dispersion of oxidized nanocellulose.

4. The method according to claim 1, characterized in that, In step (2), the wet papermaking technology includes the Kaiser process, long-wire papermaking, cylinder papermaking, or inclined wire papermaking.

5. The method according to claim 1, characterized in that, In step (3), the number of coatings or the amount of coating are controlled.

6. The method according to claim 1, characterized in that, In step (4), the temperature of the hot-press drying process is 60-120 ℃, the pressure is 2-8 MPa, and the time is 10-60 minutes.

7. A cellulose paper-based separator prepared by the preparation method according to any one of claims 1-6.

8. The cellulose paper-based separator according to claim 7, characterized in that, The cellulose paper-based separator has a three-layer composite structure, including a matrix layer composed of pulp fibers and a dense functional layer of oxidized nanocellulose covering both sides of the matrix layer.

9. A zinc-iodine battery, characterized in that, The battery comprises a cellulose paper-based separator as described in claim 7 or 8.

Citation Information

Patent Citations

  • Composite diaphragm, preparation method and application thereof, and aqueous zinc ion battery

    CN117276809A